Automated measurement of site‐specific N‐glycosylation occupancy with SWATH‐MS. Issue 13 (8th May 2015) - Xu, Ying; Bailey, Ulla‐Maja; Schulz, Benjamin L.
<x xml:space="preserve">Abstract</x> Asparagine‐linked glycosylation is a common post‐translational modification of proteins catalyzed by oligosaccharyltransferase that is important in regulating many aspects of protein function. Analysis of protein glycosylation, including glycoproteomic measurement of the site‐specific extent of glycosylation, remains challenging. Here, we developed methods combining enzymatic deglycosylation and protease digestion with SWATH‐MS to enable automated measurement of site‐specific occupancy at many glycosylation sites. Deglycosylation with peptide‐endoglycosidase H, leaving a remnant N‐acetylglucosamine on asparagines previously carrying high‐mannose glycans, followed by trypsin digestion allowed robust automated measurement of occupancy at many sites. Combining deglycosylation with the more general peptide‐N‐glycosidase F enzyme with AspN protease digest allowed robust automated differentiation of nonglycosylated and deglycosylated forms of a given glycosylation site. Ratiometric analysis of deglycosylated peptides and the total intensities of all peptides from the corresponding proteins allowed relative quantification of site‐specific glycosylation occupancy between yeast strains with various isoforms of oligosaccharyltransferase. This approach also allowed robust measurement of glycosylation sites in human salivary glycoproteins. This method for automated relative quantification of site‐specific glycosylation occupancy will be a useful tool for research with model systems and clinical samples.